Implicit differentiation and chain rule- please help

  • Thread starter SavvyAA3
  • Start date
23
0

Main Question or Discussion Point

The question and my workings are attached:
 

Answers and Replies

23
0
Sorry it seems that attachments do not upload:

Here is the Question:

Suppose R = R(q,p) = e^(q+p), where p = p(q) is defined through the equation

q^2*p+p^2*q+qp = 3

Letn r(q) = R(q,p(q)). Use the chain rule to calculate the derivative dr/dq at the point q=1.



Can you please tell me if it is correct to assume that this question is asking you to insert q^2*p+p^2*q+qp = 3 into e^(q+p), for p?

From there I have tried to derive the chain for dr/dq:

My workings:

since e^(q+q^2*p+p^2*q+qp) = 3, a constant

dr/dq = 0

so the chain
(∂R)/(∂q)*dq/(dq )+(∂R)/(∂r)*dr/(dq)= 0

 (∂R)/(∂r)*dr/(dq)= - (∂R)/(∂q)

 dr/(dq)= - (∂R)/(∂q )* (dr)/(dR)

dr/(dq)= - (∂R)/((∂q )/((∂R)/(∂r)))


I dont think this is the correct chain because I can’t find dr/dqfrom the function given.

I would be most grateful if you could point me along the correct direction for this.
Must I create two chains? i.e. one for dp/dq and then somehow incorporate this for dr/dq?

Thanks.
 

Related Threads for: Implicit differentiation and chain rule- please help

Replies
2
Views
3K
Replies
1
Views
4K
  • Last Post
Replies
10
Views
2K
  • Last Post
Replies
6
Views
596
  • Last Post
Replies
20
Views
2K
  • Last Post
Replies
4
Views
2K
  • Last Post
Replies
2
Views
2K
  • Last Post
Replies
3
Views
2K
Top